Effect of Mulching on Moisture Retention and Yield of Wheat Under rainfed Conditions - singh, Gurmel; Singhal, A.K.; Nambiar, K.K.M. (Journal of Soil and Water Conservation, 2022)
Soil moisture is one of the limiting factors for increasing the yield under rainfed conditions, particularly for wheat as there is very little rainfall received during its growth period and crop had to be grown from conserved moisture received during the preceeding monsoon period of July to September. Most of the moisture is lost through evaporation during the crop growth period from the soil. Mulches are useful in reducing this loss to a great extent and thus help in making more moisture available for crop use, which is a factor in increasing the yield. Therefore, present studies were conducted to investigate into the effect of different kinds of mulches on the moisture conservation and yield of wheat.